Unconventional diets and nutritional supplements are more common in dogs with cancer compared to healthy dogs: An online global survey of 345 dog owners. (31st May 2020) - Bianco, Adriana V.; Abood, Sarah; Mutsaers, Anthony; Woods, J. Paul; Coe, Jason B.; Verbrugghe, Adronie
Abstract: This survey aimed to investigate and compare diet type and supplement use between dogs ( Canis lupus familiaris, L.) with cancer and a population of owner‐reported healthy dogs and to assess the sources of information dog owners consult. Respondents were mainly from English‐speaking countries. Dogs were considered healthy (N = 213) if owners reported them to be in good health. Dogs were included in the cancer group (N = 132) if the owner reported that their dog had been diagnosed with cancer. An online survey was distributed to clients presenting to a tertiary oncology service, clients presenting to a local primary care veterinary practice, and through social media. Owners of dogs with cancer spent more time researching pet health ( P < .001), pet nutrition ( P < .01) and nutritional supplements ( P < .001) than owners of healthy dogs. While veterinarians were most commonly reported to be an information source for both groups, owners of healthy dogs more likely consulted pet stores and owners of dogs with cancer tended more to social media groups and blogs. Healthy dogs were more likely fed commercial dry food ( P < .001), whereas homemade cooked ( P < .001) and raw diets ( P < .05) were more prevalent among dogs with cancer. Supplement use, especially cannabidiol products, mushroom extracts or turmeric/curcumin, was also more common for this group ( P < .001). Alternative diets and supplements were more popular among owners of dogs with cancer compared to owners of healthy dogs. These findings highlight the need for nutritional counselling and education of pet owners regarding nutrition‐related topics, especially when their dog is diagnosed with cancer.